The grain market in Kazakhstan: An economic analysis of exports and domestic consumption - Assel Rakhimbekova; Aigul Mukhamejanova; Alikhan Babassov; Zhanat Abzhan; Nurgul Shaikenova (Наукові горизонти)
This study aimed to identify contemporary trends in Kazakhstan’s grain market functioning. The analysis focused on production, consumption, export, and import indicators, price dynamics, and the self-sufficiency rate of grain in Kazakhstan during 2019-2023. The research utilised official statistical data on Kazakhstan’s agricultural sector and grain market performance. A comprehensive analysis of the grain market was conducted. The statistical data analysis revealed both positive and negative trends that significantly influenced the grain market in Kazakhstan from 2019 to 2023, as well as the country’s food self-sufficiency. The findings indicated a 1.7% decline in production rates and a 16.7% reduction in industrial grain consumption, accompanied by an increase in grain usage for seeding purposes. Annual personal consumption by the population did not exceed 1.1% of the total grain utilisation in the country. A 3.9% increase in sown areas did not result in higher yields, which decreased by 9.6%. The highest yields were observed in the Qyzylorda Region, where wheat cultivation dominated. Although imports did not surpass exports, they increased more than sevenfold over time. During the study period, grain reserves in the country grew by 9%, accompanied by a significant rise in market prices. These indicators did not prevent Kazakhstan from maintaining a high level of grain self-sufficiency, enabling further development of grain exports. This research contributed new insights into the future development of the grain market in Kazakhstan, demonstrating that an export-oriented strategy combined with increased production could be a viable pathway for successful sectoral growth. This approach could mitigate the risk of a food crisis while preserving the country’s high self-sufficiency in grain